Des formes de continuité du patrimoine ethnologique : ethnologie des territoires, ethnologie du patrimoine, patrimoine culturel immatériel - Christian Hottin (In Situ)
Coming after other texts that dealt, between 2006 and 2016, the politics of ethnology at the Ministry of Culture, this article is a summary of the actions carried out during this decade, marked by the flourishing of research in the ethnology of heritage and the rise of intangible cultural heritage, but also, in 2010, at the end of the RGPP, by the abolition of the ethnological heritage department as an autonomous service. In reverse of the visions which make the diagnosis of a replacement of the ethnology by the intangible heritage, but also in opposition with the cassandres which prophesied, in anticipation and at least precipitated, the extinction of the first one, This assessment, where will not be evaded errors and hesitations, attempts to restore the spirit of synthesis between heritage and ethnology that has been at the heart of these ten years of action. The main focus of this work, the apprehension of the UNESCO convention is not separable from the other parts of this work, whether research programs, territorial action, or, well, too late, it is true, of the flattened strategy of publications Coming after other texts that dealt, between 2006 and 2016, the politics of ethnology at the Ministry of Culture, this article is a summary of the actions carried out during this decade, marked by the flourishing of research in the ethnology of heritage and the rise of intangible cultural heritage, but also, in 2010, at the end of the RGPP, by the abolition of the ethnological heritage mission as an autonomous service. In reverse of the summary visions which make the diagnosis of a replacement of the ethnology by the intangible heritage, but also in opposition with the cassandres which prophesied, in anticipation and at least precipitated, the extinction of the first, This assessment, where will not be evaded errors and hesitations, attempts to restore the spirit of synthesis between heritage and ethnology that has been at the heart of these ten years of action. The main focus of this work, the apprehension of the UNESCO convention is not separable from the other parts of this work, whether research programs, territorial action, or, well, too late, it is true, of the strategy of publications